Digital health literacy scale in older adults: A study on the validity and reliability of the Turkish version - Turan, Gulcan Bahcecioglu; Demir, Mizgin; Ozer, Zulfunaz (Mosby-Elsevier, 2026)
Background: Smart healthcare services and digital therapeutics are rapidly spreading, making digital health literacy skills critically important to benefit from these services. This is especially essential for older adults, who often need consistent health management. However, in Turkey, no suitable scale currently exists to measure digital health literacy among older adults. Therefore, This research aims to translate the Digital Health Literacy Scale to Turkish and assess its validity and reliability for elderly individuals. Method: The research was done from July 2025 to September 2025, with a total of 266 older persons monitored online. A scale including 25 items was used. Expert feedback was solicited to evaluate content validity, and the Content Validity Index (CVI) was calculated. The construct validity was assessed using the KaiserMeyer-Olkin (KMO) test, Bartlett's test, and confirmatory factor analysis (CFA). Reliability was evaluated by Cronbach's alpha, item-total correlations, and the test-retest approach. Findings: Content validity was found to be high (CVI = 0.90). The KMO test (0.868) and Bartlett's test (x(2) = 2270.041, p < 0.001) supported construct validity. The confirmatory factor analysis yielded good fit indices (RMSEA = 0.067, CFI = 0.95, TLI = 0.94). The overall Cronbach's alpha coefficient was 0.909, indicating high reliability. Test-retest reliability was also high (ICC = 0.827). Conclusion: The Turkish adaptation of the Digital Health Literacy Scale is a valid, reliable, and comprehensive instrument for assessing digital health literacy among older individuals in Turkey. This scale may provide significant insights for future research and instructional initiatives in digital health. (c) 2026 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Confirmatory Factor Analysis; Digital Health Care; Digital Health Literacy; Mobile Phone; Older Adults